PRELP secreted from mural cells protects the function of blood brain barrier through regulation of endothelial cell-cell integrity - Davaapil, Hongorzul; Hopkins, Jack; Bonnin, Nadia; Papadaki, Vasiliki; Leung, Alex; Kosuge, Hirofumi; Tashima, Takumi; Nakakido, Makoto; Sekido, Ryohei; Tsumoto, Kouhei; Sagoo, Mandeep S.; Ohnuma, Shin-Ichi (Frontiers in Cell and Developmental Biology, 2023)
Proline/arginine-rich end leucine-rich repeat protein (PRELP), is a small secreted proteoglycan expressed by pericytes and vascular smooth muscle cells surrounding the brain vasculature of adult mouse. We found that Prelp knockout mice (Prelp -/-) presented with neuroinflammation and reduced neurovasculature integrity, resulting in IgG and dextran leakage in the cerebellum and cortex. Histological analysis of Prelp -/-mice revealed reduced cell-cell integrity of the blood brain barrier, capillary attachment of pericytes and astrocyte end-feet. RNA-sequencing analysis found that cell-cell adhesion and inflammation are affected in Prelp -/-mice and gene ontology analysis as well as gene set enrichment analysis demonstrated that inflammation related processes and adhesion related processes such as epithelial-mesenchymal transition and apical junctions were significantly affected, suggesting PRELP is a regulator of cell-cell adhesion. Immunofluorescence analysis showed that adhesion junction protein expression levels of cadherin, claudin-5, and ZO-1, was suppressed in Prelp -/-mice neurovasculature. Additionally, in vitro studies revealed that PRELP application to endothelial cells enhances cell-cell integrity, induces mesenchymal-endothelial transition and inhibits TGF-b mediated damage to cell-cell adhesion. Our study indicates that PRELP is a novel endogenous secreted regulator of neurovasculature integrity and that PRELP application may be a potential treatment for diseases associated with neurovascular damage.